Women’s contribution to climate change action: A gender analysis - Setyowati Retno; Rusdiyana Eksa; Widiyanto; Sugihardjo; Lestari Eny; Arwindianti Micelle Lovinia (BIO Web of Conferences)
Women’s participation in the Climate Village Program will not only strengthen village resilience to climate change, but also accelerate the achievement of sustainable development goals (SDGs), especially those related to gender equality, poverty alleviation, and environmental protection. This research aims to analyze the women’s participation and role in proklim in Karanganyar Regency, Central Java Province. This research used a descriptive qualitative approach. Data were collected through interviews, field observation, documentation, and focus group discussion (FGD). Informants consisted of local activist, forestry extensionist, agricultural extensionist, health care service office, village government, farmer group, female farmer group, Family Welfare Program (FWP), and youth organization (Karang Taruna). Data validation was carried out using source and method triangulations. The finding of research indicates that women are present not only to help but also to be the main activist of proklim activities. This movement is embodied into such institutions as female farmer group, Family Welfare Program (FWP), and waste bank driven by women through activities food production from the surrounding environment, healthy (organic) farming practices, health education and environmental hygiene, basic health services (posyandu for toddlers, adolescents and elderly), prevention of infectious diseases through “Jumantik”, waste reduction education, education on circular economy utilization of waste, making biopores and utilizing organic waste (magot cultivation).